2021
DOI: 10.3390/pathogens10070821
|View full text |Cite
|
Sign up to set email alerts
|

Rhipicephalus Tick: A Contextual Review for Southeast Asia

Abstract: Rhipicephalus species are distributed globally with a notifiable presence in Southeast Asia (SEA) within animal and human populations. The Rhipicephalus species are highly adaptive and have established successful coexistence within human dwellings and are known to be active all year round, predominantly in tropical and subtropical climates existing in SEA. In this review, the morphological characteristics, epidemiology, and epizootiology of Rhipicephalus tick species found in SEA are reviewed. There are six co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 133 publications
0
12
0
Order By: Relevance
“…In this study, we reported Rhipicephalus turanicus in dogs. A previous study reported that the prevalence rate of Rhipicephalus sanguineus and Hyalomma anatolicum in Punjab was about 25% (42,45). Similar results for Hyalomma, Rhipicephalus, and Haemaphysalis were reported by a study on livestock in Pakistan (15,(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we reported Rhipicephalus turanicus in dogs. A previous study reported that the prevalence rate of Rhipicephalus sanguineus and Hyalomma anatolicum in Punjab was about 25% (42,45). Similar results for Hyalomma, Rhipicephalus, and Haemaphysalis were reported by a study on livestock in Pakistan (15,(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Rhipicephalus are known as brown dog tick. The highest rate of Rhipicephalus is due to presence of dogs and cats near to buffaloes and cows (42). Haemaphysalis was more prevalent in goats (46.9%), followed by sheep (42.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The Rhipicephalus ticks hold economic importance, having a broad coverage of hosts including mammals, reptiles, and avian species [ 20 ]. The parasite adaptation in Rhipicephalus ticks has made them successful parasites of public health importance [ 1 ]. Rhipicephalus ticks are known for high genetic diversity, enabling them to thrive in different geographical regions of the world [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhipicephalus ticks are economically important ticks of bovines, acting as vectors of protozoal (babesiosis and theileriosis), bacterial (anaplasmosis), viral (Thogoto), and rickettsial diseases [ 1 ]. Similarly, the diseases of ovine (Nairobi sheep disease, babesiosis, theileriosis, anaplasmosis, and rickettsiosis) present challenges for their effective prevention and control [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…B. bovis , B. bigemina , and A. marginale have the same biological vector, the Rhipicephalus spp. tick, which is the predominant cattle tick in Thailand [ 35 ]. In this study, the coinfection combination of T. orientalis and A. marginale was the most frequently recorded.…”
Section: Discussionmentioning
confidence: 99%